Applications and Challenges of Sweetener in Ice Cream - You, Kaiming (Transactions on Environment, Energy and Earth Sciences, 2024)
As the global obesity problem continues to deepen, consumers' pursuit of healthy, low-sugar and low-fat foods is also gradually deepening, so the production of new low-sugar ice cream is also gradually concerned. In the continuous innovation and research of manufacturers and researchers, many low-sugar ice cream have been made and innovated, but many of them have various problems, such as the lack of taste and flavor, safety and so on. This review will focus on different kinds of sweeteners and their characteristics and classification, and analyze the application of sweeteners in ice cream, analyze the advantages and disadvantages of sweeteners in the application process of ice cream. This paper sorted out and classified the application of sweeteners in ice cream by subsequent researchers, and analyzed the existing problems. Further confirmation, research and continuous improvement are needed on the taste, flavor and safety of sweeteners. In future research, further analysis of sweeteners is needed, analysis of different problems, and further innovation, innovation of new sweeteners and different kinds of compounding.